(3EJMGa PQjI SjOj Ydj GdHgdhd HCSGfjO LhGeY CMGOjK GdQShd Udi Gddg Ydjg hSdes - (3CHh GdCeOGO HQgGf GdOjf EHQGgje Hf EHQGgje Hf MSf Hf Ydj Hf YHO GdbOhS GHf eMeO Hf gGQhf GdeYQha HGddbGfj GdeGdcj,J (B1041 (3g` s
(3ChdgG (B:s
(3GdMeO dg QH GdYGdejf MeO YHO UM hUdg aSdSd YHQGJ GdfOe ai ebGe GdTghO s
(3BNQgG (B:s
(3QHfG dGJRZ bdhHfG HYO EP gOjJfG hgH dfG ef dOfc QMeI Efc CfJ GdhgGH s
(3hgPG GdcJGH ELGRI ef GdeDda ddYGQa HGddg CHj SYjO YHOGdQMef Hf Ydi GdHgdhds
(3hgPg GdELGRI HJGQjN SfI (B1029 (3g` ELGRI HeQhjGJg ef GdMOjK hZjQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B28 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B2s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B247 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B9 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs